PEMANFAATAN ECENG GONDOK Eichhomia crassipes (Mart) Solm SEBAGAI TEKNIK ALTERNATIF DALAM PENGOLAHAN BIOLOGIS AIR LIMBAH ASAL RUMAH PEMOTONGAN HEWAN (RPH) PESANGGARAN DENPASAR - BALI - IW Suardana (Research Center for Biology-Indonesian Institute of Sciences, 2009)
A part from its main product, meat, a slaughterhouse also produces by products and waste. The waste from slaughterhouse is categorized as organic waste, which is high in proteins, fats, and starches. This waste is potential as a source of pollutant. Slaughterhouse wastes can be treated by physically, chemically, and biologically.One of biological treatments is the use of water hyacinth (Eichhomia crassipes (Mart) Solm.), which is known to have an ability to remove organic and unorganic compound and heavy metals.The objective of this research was to evaluate the wastewater quality with water hyacinth treatment and to identify the interaction between action period and the density of water hyacinth during treatment. Four model ponds of 95 cm long x 50 cm wide x 50 cm high were used in this research. The parameters observed were pH, BOD5, and COD for the water quality. Each parameter was observed on day 0, 7, 14, 21, and 28, respectiv ely. The results of the research indicates that the water hyacinth had significant effect (P<0.01) on declining pH, BOD5 and COD of wastewater. The interaction between treatment and time observation lh showed significant effect (P<0.01) up to 28Â day of observation.